PENERAPAN PEMBELAJARAN BERBASIS PROYEK PADA MATERI TRANSFORMASI GEOMETRI - Ratnawati, Oktaviana Ainun; Haryani, Desti; Ali Hasan, Qodri; Artuti, Emy; ., Pancarita (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Palangka Raya, 2023)
The success of implementing the PjBL learning model in the classroom lies in the teacher's ability to effectively design learning, motivate, support and guide students in the process of determining and completing the project. The aim of this research is to apply project-based learning (PjBL) to Geometry Transformation material for class IX junior high school students to find out how the learning process is perceived by students and teachers. This type of research is descriptive research with the research subjects being class IX middle school students. The research instrument is a lesson plan for 6 meetings, posttest, and mathematics disposition. The results of the research show that the implementation of the PjBL learning model in the classroom is less than optimal, as shown by the students' posttest results which have decreased compared to the pretest scores conducted by the teacher, the mathematics disposition questionnaire has also decreased. However, the project assignments in the form of videos and paintings for each group were completed well. The decrease in grades occurred because conditions at the research location experienced a disaster, namely